The effect of biosimilar administration on clinical outcomes in patients with adalimumab‐controlled psoriasis. Issue 4 (18th September 2021) - Panahi, M.; Skelly, Y.; Zaman, R.
Abstract: Background: Adalimumab is an anti‐tumour necrosis factor administered for the management of severe psoriasis. Previously limited to Humira, new biosimilar medications have now emerged including Amgevita. To date, there have been no comparison studies of adalimumab biosimilar use on different types of psoriasis. Objective: To investigate the implications of biosimilar medications and patient specific factors on clinical outcomes, including Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI) scores. Methods: A clinical notes review was performed for all dermatology patients with adalimumab‐controlled psoriasis at our centre. Demographic profile, psoriasis subtype and changes in clinical patterns as demonstrated by PASI and DLQI were extracted and analysed. Results: Of 91 records identified, 70 patients met the inclusion criteria. 21 patients (30%) demonstrated significant increase in PASI and DLQI scores with Amgevita. Scores improved to baseline once Humira was restarted. Findings reveal no difference in pre‐adalimumab disease severity or mean age between the groups. Patients responding only to Humira had a greater proportion of females, and were likelier to have psoriatic arthritis (odds ratio [OR]: 10.63; p < 0.0002) and nail involvement (OR: 6.13, p < 0.02), compared with patients well controlled with Amgevita. Conclusions: This audit of a single dermatology centre suggests switching to a biosimilar adalimumab may exacerbate symptoms of psoriasis. Future studies should investigate whether findings are restricted to our study population, and consider the influence of other factors, such as disease subtypes and medication formulations. Abstract : Clinical outcomes of patients with adalimumab‐controlled psoriasis administered Humira and its biosimilar Amgevita were compared. Patients responding only to Humira had a greater proportion of females, and were likelier to have psoriatic arthritis (odds ratio (OR): 10.63; p < 0.0002) and nail involvement (OR: 6.13, p < 0.02), compared with patients well controlled with Amgevita. This audit supports our re‐trialling of biosimilar drugs prior to switching biological class in patients with psoriatic arthritis.